Analisis Daya Saing Crude Palm Oil (CPO) Indonesia Di Pasar Internasional` - Sopia Azida; Muhammad Yamin; Riswani Riswani (Agriculture Faculty of Flores University, 2023)
This study aims to evaluate Indonesia's competitiveness and assess the dynamics of Indonesia's CPO performance in the international market. Comparative CPO in Indonesia is carried out using the